Persepsi Guru Pondok Pesantren Assalafiyah Nurul Hidayah Pangkalpinang terhadap Bank Syariah - Romariyah Romariyah; Tinggal Purwanto; Reka Meilani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the perceptions of teachers at Pondok Pesantren Assalafiyah Nurul Hidayah Pangkalpinang regarding Islamic banking. Despite the religious background of the teachers, the findings reveal that the majority still use conventional banks due to limited knowledge about Islamic banking principles, lack of socialization, and practical reasons such as convenience and proximity. The research uses a qualitative descriptive method involving 21 teachers through in-depth interviews, observations, and documentation. The results indicate that while the teachers have a generally positive view of Islamic banking, their understanding remains partial, particularly regarding profit-sharing mechanisms, riba prohibition, and Islamic financial products. Moreover, their interest in saving at Islamic banks is potential but requires further education and socialization to encourage real participation. This research highlights the need for more proactive promotion and financial literacy programs from Islamic banking institutions to increase public awareness, especially among religious educators, regarding the use of sharia-compliant financial services.